KESANTUNAN TINDAK TUTUR LISAN - Winarsih, Suko (Pusat Pengembangan Bahasa IAIN Tulungagung, 2011)
Effective communication requires the mastery not only of grammar and lexicon but also of non-linguistic factors, such as knowing when and how it is appropriate to open a verbal communication, what appropriate topics and forms of address are to be used to whom and in what situation or condition. A verbal communication refers to any interactional talks involving at least two participants, a speaker and a listener, and they change roles. The conversation takes place in non-formalized setting, with no special rules of conversations. A verbal communication is a kind of talk most frequently and normaly found in real life. The widest context of the verbal communication is called speech community. A speech community is a group of people who do not share the same language, but share a set of norms and rules for the use of language. The speech communities are essesntially social rather than linguistic because it is cultural bounded. It means that every speech community has its own politeness in doing conversation.